CRITICAL ANALYSIS ON MAXIMIZING DIAGNOSTIC ACCURACY AND TIMELINESS IN SYNERGY BETWEEN EMERGENCY MEDICAL SERVICES, NURSING CARE, AND MEDICAL LABORATORIES - 1Bassam Lahi M Alsharari, 2Nedal Lahi M Alsharari, 3Ghazi Alnashmialsharari, 4Aqla Salem A Alsharari, 5Abdulrahman Owaidalsharari, 6Mohammed Hameedsalamahalsharari, 7Fawaz Subaihdebian Al Dhabani, 8Bandar Musaedalslrhani, 9Zead Madailahalenzi,; 10Mohammed Shaluf S Alsharari, 11Hani Dhaheralsharari 12Abdulelah Saadkurdialanazi, 13Ali Salem Nasser Almansour (Chelonian Research Foundation, 2022)
This article presents techniques and challenges to make strides in the exactness and convenience of coordination between EmergencyMedical Services (EMS), nursing, and offices. He emphasized the significance of cooperation in giving quality, patient care. Key challenges incorporate constrained assets, communication obstructions, and changeability in testing. Openings for enhancement lie within the integration of research facilities, telemedicine, and clinical conventions. Improvements such as electronic information recovery, back-channel communication, and data sharing. Optimization, calculation of the logical show, and getting to the framework are the premises for the victory of inspecting ventures. The library's charts, graphs, and outlines are outlined to help understand these concepts and highlight the significance of collaboration in achieving clinical results. Keywords: Diagnostic accuracy, timeliness, emergency Medical Services, Nursing care, Medical laboratories, Interdisciplinary collaboration, Technology, Continuous quality improvement